Regulation of enteroendocrine cell respiration by the microbial metabolite hydrogen sulfide - Larraufie, Pierre; Haroun, Kenza; Fleury, Carla; Andriamihaja, Mireille; Blachier, François (Frontiers in Endocrinology, 2023)
Endocrine functions of the gut are supported by a scattered population of cells, the enteroendocrine cells (EECs). EECs sense their environment to secrete hormones in a regulated manner. Distal EECs are in contact with various microbial compounds including hydrogen sulfide (H2S) which modulate cell respiration with potential consequences on EEC physiology. However, the effect of H2S on gut hormone secretion remains discussed and the importance of the modulation of cell metabolism on EEC functions remains to be deciphered. The aim of this project was to characterise the metabolic response of EECs to H2S and the consequences on GLP-1 secretion. We used cell line models of EECs to assess their capacity to metabolize H2S at low concentration and the associated modulation of cell respiration. We confirmed that like what is observed in colonocytes, colonic EEC model, NCI-h716 cell line rapidly metabolizes H2S at low concentrations, resulting in transient increased respiration. Higher concentrations of H2S inhibited this respiration, with the concentration threshold for inhibition depending on cell density. However, increased or inhibited oxidative respiration had little effect on acute GLP-1 secretion. Overall, we present here a first study showing the EEC capacity to detoxify low concentrations of H2S and used this model to acutely address the importance of cell respiration on secretory activity.